MiR-4733-5p promotes gallbladder carcinoma progression via directly targeting kruppel like factor 7. Issue 4 (1st April 2022) - Hu, Xiaoqiang; Zhang, Junzhe; Bu, Junfeng; Yang, Kaini; Xu, Sunwang; Pan, Mengqiao; Xiang, Dongxi; Chen, Wei
ABSTRACT: Gallbladder carcinoma (GBC) is highly aggressive with poor prognosis. Accumulating reports show that miRNAs play critical roles in tumor progression. Previous studies have identified several miRNAs that promoted or inhibited GBC cell proliferation and/or metastasis. Here, we used the Gene Expression Omnibus (GEO) dataset to identify dysregulated miRNAs in GBC, followed by validating the upregulation of the miR-4733-5p and downregulation of kruppel-like factor 7 (KLF7) in GBC biopsies by quantitative real-time PCR (RT-qPCR), in situ hybridization (ISH) staining, and immunohistochemistry (IHC) assays. GBC cell proliferation and invasion capacities mediated by miR-4733-5p were evaluated by a series of function assays in vitro, including CCK-8, colony formation assay, wound healing assay and transwell assay. Xenograft tumor model found that miR-4733-5p promoted GBC tumor growth in vivo . This study clarified that miR-4733-5p was upregulated in GBC and promoted GBC cell proliferation via directly binding to 3' untranslated region (UTR) of KLF, which was downregulated and prohibited the proliferation and migration of GBC cells. Graphical abstract: uf0001